(untitled) (Islas, 2025)
Introduction: This study analyzes the actions of the Revolutionary Communist League (LCR) and the Internationalist Communist League (LCI) during key moments of Spain’s Transition and the Portuguese Revolution. The article explores their political positions during major events, as well as their interactions with other political, union, and social forces. Methods: The research is based on primary digital sources from digital archives and documents collected from physical archives. These documents are contextualized using updated literature for both cases. Results: The article traces the trajectory of the investigated organizations through the main events of the Carnation Revolution and Spain’s Transition. It examines their specific interactions with social movements of the time and their engagement with major political milestones in both countries. Conclusions: After analyzing both organizations and their actions within their respective contexts, it can be concluded that they developed a very similar political culture. These similarities stem from both their comparable historical contexts and their affiliation with the same International.